Social work in a globalizing world - Dominelli, Lena. (Cambridge, UK ; Malden, MA : Polity, 2010)
Written by a leading social work academic whose work is internationa lly renowned, this book confronts contemporary challenges facing social workers in relation to globalization and the rise of international glo bal problems.
Introduction -- Creating the new profession of social work -- Mappin g out the terrain of 'the social' -- Professionalization, practice meth ods and processes of intervention -- Social work, citizenship, human ri ghts and social justice -- Human, social and environmental degradation -- Globalizing the local and localizing the global in practice -- Concl usions.
Includes bibliographical references (p. [174]-195) and indexes.
Keywords: Social service; Globalization -- Social aspects